2018
DOI: 10.1080/07420528.2018.1488259
|View full text |Cite
|
Sign up to set email alerts
|

Constant light alters serum hormone levels related to thyroid function in male CD-1 mice

Abstract: Disruptions to the circadian rhythm can lead to altered metabolism. Modification of thyroid function may be a reason why circadian misalignment may contribute to future metabolic disorders. We investigated whether circadian disruption through constant light (LL) can lead to variations in hormone levels associated with thyroid function. Mice were exposed to LL or a 12:12 Light:Dark (LD) cycle for 6 weeks; then glucose tolerance and thyroid hormone levels were measured at ZT 6 and ZT 18. There was day/night vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…This effect was even more apparent at higher intensities since 50% of mice were arrhythmic after exposure to >500 lx [ 92 ]. These findings were supported by other studies where the free-running rhythm with a lengthened period and the reduced strength of the rhythm appeared under LL of ≥180 and 100 lx [ 61 , 75 ], while the arrhythmicity occurred under much higher intensity (~580 lx) [ 72 ]. On the other hand, mice exposed to low illumination also developed arrhythmic locomotor activity without changes in total 24 h activity, but the experiment lasted two times longer [ 62 ].…”
Section: Locomotor Activity Food Intake and Body Masssupporting
confidence: 83%
See 2 more Smart Citations
“…This effect was even more apparent at higher intensities since 50% of mice were arrhythmic after exposure to >500 lx [ 92 ]. These findings were supported by other studies where the free-running rhythm with a lengthened period and the reduced strength of the rhythm appeared under LL of ≥180 and 100 lx [ 61 , 75 ], while the arrhythmicity occurred under much higher intensity (~580 lx) [ 72 ]. On the other hand, mice exposed to low illumination also developed arrhythmic locomotor activity without changes in total 24 h activity, but the experiment lasted two times longer [ 62 ].…”
Section: Locomotor Activity Food Intake and Body Masssupporting
confidence: 83%
“…Constant light did not influence total 24 h food intake [51,61,62,[73][74][75], but the daily variation was suppressed mostly due to increased food consumption in mice during the subjective day [51,61,62,73,74]. On the other hand, total food intake was reduced in mice fed a high-fat diet [61].…”
Section: Food Intake and Body Mass Under Constant Lightmentioning
confidence: 88%
See 1 more Smart Citation
“…Regardless of the previously listed strain differences found in their responses to continuous light exposure, this study provides additional evidence that LL can produce negative metabolic effects overall, including increased liver triglycerides and different fT4 levels, despite similar levels of food consumption. A recent study from our lab also reported altered fT4 and other hormone levels related to obesity and thyroid function in male CD-1 mice exposed to LL, even in the absence of weight gain or increased food consumption (Maroni et al, 2018). In summary, these results illustrate that circadian disruption can lead to significant changes in metabolic phenotypes even if a healthy diet is consumed.…”
Section: Discussionsupporting
confidence: 71%
“…In hamsters under short-day photoperiod, low levels of ALAN elevated the levels of thyroid-stimulating-hormone (TSH) receptors causing advanced W b and gonadal growth [112]. Continuous exposure to ALAN decreased TSH, but increased both T3 and T4 in mice [113]. In birds, long-term exposure to ALAN increased both the blood levels of the thyroid hormones and W b [114].…”
Section: Physiological and Epigenetic Responses To Melatonin And Thyrmentioning
confidence: 99%